A Bishop Saving ‘Singers’: Tales of Torture in Pinochet's Chile - Frenz, Helmut (Dialog, 2008)
The article provides a brief biographical introduction of Lutheran Bishop Helmut Frenz, co-founder of the Committee for Peace, credited with saving at least 6,000 lives of persecuted Chileans following the September 1973 military coup at the hands of the brutal general Agosto Pinochet. Excerpts from Frenz' book, Mi Vida Chilena, document Pinochet's acknowledgment that torture was the regime's official policy, and share the poignant story of one suspected leftist's brutal torture.